Synthesis, Characterization and Crystal Structures of Hydrazone Compounds Derived from Cyanoacetohydrazide - Zhang, Wei-Ming; Qian, Shao-Song; You, Zhonglu (Asian Journal of Chemistry, 2014)
Two new hydrazone compounds, 2-cyano-N'-(3-ethoxy-2-hydroxybenzylidene)acetohydrazide (1) and 2-cyano-N'-(2-methoxybenzylidene)-acetohydrazide (2), were prepared and structurally characterized by elemental analysis, IR and UV-visible spectra and single crystal X-ray determination. Compound 1 crystallizes as monoclinic space group P21/c, with unit cell dimensions a = 19.573(7) Å, b = 9.620(4) Å, c = 13.731(5) Å, b = 110.372(4)º, V = 2423.8(15) Å3, Z = 8, R1 = 0.1047 and wR2 = 0.2767. Compound 2 crystallizes as monoclinic space group P21/c, with unit cell dimensions a = 4.503(2) Å, b = 10.066(3) Å, c = 24.435(3) Å, b = 95.29(2)º, V = 1103.0(5) Å3, Z = 4, R1 = 0.0430 and wR2 = 0.0978. Crystal of the compounds are stabilized by hydrogen bonds and p···p interactions.